THREE DIMENSIONAL VISUALIZATION OF AGAPE WONOSOBO BASIC SCHOOL BUILDING WITH LOWPOLY METHOD - Bayu Aji Santoso (Institut Teknologi Dirgantara Adisutjipto, 2018)
Creation of 3D object can use a variety of software, one of them using the software Blender. As for the methods in the creation of 3D objects lowpoy and highpoly, among others. Visualization is the process of delivery of information is presented in a 3D visual object so that it looks more interesting and more real, therefore made Building visualization SD Agape Wonosobo which is expected to be utilized by the Foundation for the help the depiction of the building be constructed SD Agape. Creation of 3D objects in this research method using lowpoly. From the results of testing done 3D visualization applications can help visualize building SD Agape will be built, the time you access it based on Browser used most quickly using the Firefox Browser, while based on computers with different time specifications have been influenced from the processor and ram are available the higher faster access time specification, this visualization applications can not be run in an unsupported Browser WebGL.